Concurrent Anti-glomerular Basement Membrane Nephritis and IgA Nephropathy - Kwang-Sun Suh; Song-Yi Choi; Go Eun Bae; Dae Eun Choi; Min-kyung Yeo (Korean Society of Pathologists & the Korean Society for Cytopathology, 2019)
Anti-glomerular basement membrane (GBM) nephritis is characterized by circulating anti-GBM antibodies and crescentic glomerulonephritis (GN) with deposition of IgG along the GBM. In a limited number of cases, glomerular immune complexes have been identified in anti-GBM nephritis. A 38-year-old female presented azotemia, hematuria, and proteinuria without any pulmonary symptoms. A renal biopsy showed crescentic GN with linear IgG deposition along the GBM and mesangial IgA deposition. The patient was diagnosed as concurrent anti-GBM nephritis and IgA nephropathy. Therapies with pulse methylprednisolone and cyclophosphamide administration were effective. Concurrent cases of both anti-GBM nephritis and IgA nephropathy are rare among cases of anti-GBM diseases with deposition of immune complexes. This rare case of concurrent anti-GBM nephritis and IgA nephropathy with literature review is noteworthy.